2013
DOI: 10.1037/a0034002
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of atypical processing underlying mental set shifting in ecstasy polydrug and polydrug users.

Abstract: Executive functioning deficits are reported in ecstasy users. However research into mental set switching has been equivocal, with behavioural studies suggesting the function is preserved.The current study sought to address the issue of switching deficits in ecstasy users by combining behavioural performance with electrophysiological correlates (EEG). Twenty ecstasy polydrug users, 20 non-ecstasy polydrug users and 20 drug naive controls were recruited. Participants completed questionnaires about their drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This suggests that ecstasy users work harder to achieve similar performance to controls, and that functional differences may be apparent with increased workload. Similar conclusions have been drawn from electroencephalogram studies whereby ecstasy users display evidence of recruiting additional resources in comparison with controls, whilst showing similar performance (Burgess et al 2011 ; Roberts et al 2013 a , b , c ). Similarly, functional magnetic resonance imaging (fMRI) studies have shown alterations to neuronal activation consistent with ecstasy-related damage despite not showing any performance deficits (Moeller et al 2004 ; Daumann et al 2005 ; Jager et al 2008 ; Roberts & Garavan, 2010 ).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This suggests that ecstasy users work harder to achieve similar performance to controls, and that functional differences may be apparent with increased workload. Similar conclusions have been drawn from electroencephalogram studies whereby ecstasy users display evidence of recruiting additional resources in comparison with controls, whilst showing similar performance (Burgess et al 2011 ; Roberts et al 2013 a , b , c ). Similarly, functional magnetic resonance imaging (fMRI) studies have shown alterations to neuronal activation consistent with ecstasy-related damage despite not showing any performance deficits (Moeller et al 2004 ; Daumann et al 2005 ; Jager et al 2008 ; Roberts & Garavan, 2010 ).…”
Section: Introductionsupporting
confidence: 68%
“…However, some studies have observed significant switching differences between ecstasy users and controls (Halpern et al 2004 ; Dafters, 2006 a ) and neuroimaging studies have suggested atypical processing during switching (Roberts et al . 2013 c ). This highlights the necessity for larger samples to elucidate this performance deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were generally healthy young men who were recruited through social media and telephone advertisements. Inclusion criteria were as follows: (1) Community-dwelling young men aged 18-30 years; (2) no cognitive impairments; (3) Montreal Cognitive Assessment (MoCA) score � 24; (4) ability to read Chinese characters; (5) normal or corrected-tonormal vision; (6) had enough sleep the day before the experiment; (7) middle to high physical activity levels as determined by the International Physical Activity Questionnaire (IPAQ); (8) received a good education (high school degree and above), could understand simple English words. Exclusion criteria were as follows: (1) color blindness or deficiency in color vision; (2) any severe cardiopulmonary disease; (3) any musculoskeletal difficulties that prevent exercise or other movement disorders; (4) taking of any medication during the intervention period that could impair cognitive function; and (5) alcohol consumption within 24 hours before the experiment.…”
Section: Participantsmentioning
confidence: 99%
“…Inhibition control is the ability to voluntarily suppress task-irrelevant responses in favor of task-relevant goal-directed responses [ 4 ]. Mental set shifting is the ability to switch attention between multiple tasks, operations, or mental sets [ 5 ]. Information updating involves continuously modifying the content of working memory as new information comes in [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method is commonly used in this research area (Montgomery et al, 2005: Roberts et al, 2015. Where objective measures of substance use have been collected in our previous work, low levels of recent use were found in participants' urine, and exclusion of participants with positive screens did not change the significant effects (Roberts et al, 2013).…”
Section: Inspection Ofmentioning
confidence: 99%